Penta Helix’s Perspective: The Green Tourism at the Tourist Village in Bali, Indonesia - OKA, I Made Darma; ANTARA, Dewa Made Suria; RUKI, Made; KANAH, Kanah; DARMAYANTI, Putu Widya (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022DO - 10.14505/jemt.v13.3(59).25, 2022)
This study explores the implementation of the green tourism (GT) in the tourist village in Bali using Penta Helix perspective. The data were collected through observation, interview and library research. The informants were determined using the sampling purposive method. The data were analysed using mixed method. The result shows that the GT has been well implemented in the tourist village, as shown by the following things: the tourist village has been developed by preserving the environment; the tourist village has been able to improve the vitality of the local economy; the tourist village has been able to maintain the cultural diversification; and the tourist village has been able to introduce new experience to tourists. The result shows that the environmental, the local economic, the culture and experience achievement contribute to the GT .